Improving the pedagogic competence of Pandhega Jaya Christian High School teachers through making learning videos - Erly Grizca Boelan; Anselmus Boy Baunsele; Aloisius Masan Kopon; Maria Benedikta Tukan; Maria Aloisia Uron Leba; Faderina Komisia (University of Merdeka Malang, 2022)
The development of technology today has had a very significant impact in the world of education, one of which is the creation of innovative learning media so that it can be a solution for teachers in creating a more interesting learning atmosphere. In line with this, teachers must be able to adapt, one of which is increasing their competence, especially pedagogic competence. The objectives of this activity are 1) to improve teacher learning and creativity in preparing media; and 2) solving problems faced by teachers in making learning videos; and 3) introducing software/applications that are easy to use in making learning videos. This service activity was carried out at Pandhega Jaya Christian High School as a partner school. The method of service used is in the form of training. The stages of training activities include: preparation, implementation, monitoring and evaluation. The result of this activity is an increase in the ability of teachers to use technology-based media. This can be seen from the teachers being able to make learning videos using an android/ios-based application, namely Capcut. The whole series of activities went well and the participants looked so enthusiastic and followed the whole series of activities to completion.